n=1時,左=1-1/2=1/2 右面=1/2成立,
假設n=k時,成立:1-1/2+1/3-1/4+...+1/2k-1-1/2k=1/k+1+1/k+2+...+1/k+k
則n=k+1時,
右=1/(k+2)+1/(k+3)+...+1/(k+1+k)+1/(2K+2)
=1/(k+2)+1/k+3)+...+1/(2k+1)+1/(2k+2).........................1
左=[1-1/2+1/3-1/4+...+1/2k-1-1/2k]+1/(2k+1)-1/(2k+2)
=1/(k+1)+1/(k+2)+...+1/(k+k)+1/(2k+1)-1/(2k+2)
=1/(k+2)+1/(k+3)+...+(2k+1)+1/(k+1)-1/(2k+2)
=1/(k+2)+1/(k+3)+...+(2k+1)+(2k+2-k-1)/[(k+1)(2k+2)]
=1/(k+2)+1/(k+3)+...+(2k+1)+(k+1)/[(k+1)(2k+2)]
=1/(k+2)+1/(k+3)+...+(2k+1)+1/(2k+2).............................2
1式=2式
所以n=k+1時也成立,
所以原式成立。
n=1時,左=1-1/2=1/2 右面=1/2成立,
假設n=k時,成立:1-1/2+1/3-1/4+...+1/2k-1-1/2k=1/k+1+1/k+2+...+1/k+k
則n=k+1時,
右=1/(k+2)+1/(k+3)+...+1/(k+1+k)+1/(2K+2)
=1/(k+2)+1/k+3)+...+1/(2k+1)+1/(2k+2).........................1
左=[1-1/2+1/3-1/4+...+1/2k-1-1/2k]+1/(2k+1)-1/(2k+2)
=1/(k+1)+1/(k+2)+...+1/(k+k)+1/(2k+1)-1/(2k+2)
=1/(k+2)+1/(k+3)+...+(2k+1)+1/(k+1)-1/(2k+2)
=1/(k+2)+1/(k+3)+...+(2k+1)+(2k+2-k-1)/[(k+1)(2k+2)]
=1/(k+2)+1/(k+3)+...+(2k+1)+(k+1)/[(k+1)(2k+2)]
=1/(k+2)+1/(k+3)+...+(2k+1)+1/(2k+2).............................2
1式=2式
所以n=k+1時也成立,
所以原式成立。